Donor N‐Substitution as Design Principle for Fast and Blue Luminescence in Carbene‐Metal‐Amides. Issue 15 (20th May 2022) - Reponen, Antti‐Pekka M.; Chotard, Florian; Lempelto, Aku; Shekhovtsev, Vitalii; Credgington, Dan; Bochmann, Manfred; Linnolahti, Mikko; Greenham, Neil C.; Romanov, Alexander S.
Abstract: A series of gold‐centered carbene‐metal‐amide (CMA) complexes are synthesized with the carbazole donor ligand modified by substitution with nitrogen atoms in varying positions. The luminescence of new aza‐CMA complexes shows a significant blueshift depending on the position of the N atom, to provide bright blue‐green (500 nm), sky‐blue (478 nm), blue (450 nm) and deep‐blue (419 nm) light‐emitters. The impact of the electron‐withdrawing aza‐group on the nature of the luminescence and the excited state energies of the locally excited (LE) or charge transfer (CT) states have been interpreted with the help of transient absorption, in‐depth photoluminescence experiments and theoretical calculations. By considering the orbital characters of the lowest CT and LE states, we develop a new concept for simultaneous energy tuning for both of these states with a single aza‐substitution, allowing for fast and blue CT emission. This concept allows the interference of 3 LE phosphorescence to be avoided at room temperature. The approach is extended to two N substitutions at the optimal location in the 3‐ and 6‐positions of the carbazole skeleton. These results suggest a practical molecular design towards the development of bright and deep‐blue emitting CMA materials to tackle the stability problem of energy‐efficient deep‐blue OLEDs. Abstract : Gold‐centered carbene‐metal‐amide materials with nitrogen substitution at various positions of the carbazole donor allow systematic control and variation of the charge transfer and locally excited states. Aza‐substitution in para‐position of the carbazole is a reliable strategy to realize bright, fast, and deep‐blue luminescent materials while maintaining the charge transfer character of the emission mechanism.